An investigation on the serodetection of Dengue virus in Sabah, Malaysian Borneo - Zulina Mazlan (2019)
Background: Dengue is re-emerging mosquito-borne infection and one of significant public health concern and has been expanding its distribution in a various part of the world. Dengue cases were more common in tropical and subtropical regions of the world. Dengue infection is endemic disease and can be transmitted by blood transfusion. Malaysia is one of the severe dengue-endemic country in Southeast Asia with the presence of all four serotypes (DENV1, DENV2, DENV3, DENV3, DENV4). Secondary infection of DENV infection by different DENV serotype from primary infection increase the risk for DHF and DSS and mostly related to antibody dependent enhancement (ADE) and transfusion of blood or blood product is one of the dengue treatments increase the blood transfusion safety measured. Periodically seroprevalence study can be used to understand the real burden of dengue in Malaysia population since many cases of dengue is unreported and the total cases of dengue don't reflect the actual dengue situation burden in the population and also marking the readiness of Sabah population for dengue vaccine implementation according to WHO recommendation. The objective of the study is to determine the rate of dengue seroprevalence among healthy adult's population from Sabah, Malaysia. Methods: A prospective cross-sectional study was conducted on blood donor samples from December 2016 to August 2017. This research was approved by the Medical Research & Ethics Committee (MREC), Ministry of Health, Malaysia and Research and Ethical Committee University Malaysia Sabah. Serum samples from 364 eligible blood donors were collected from Sabah Women and Children Hospital (SWACH) age 18-65 years and examined for the presence of dengue-specific immunoglobulins G (IgG) using enzyme-linked immunosorbent assay (ELISA) according to manufacturer's protocol. The ABO group of the blood donor were identified by agglutination test according to manufacturer protocol. Data were entered and statistically analyzed by SPSS, Version 24 (IBM) for gender, age, ethnicity, localities area, blood grouping and the results of dengue IgG. Results: Majority of the resident having previous dengue infection belong to the age group of 18 to 65 years was 36.5% (N=133, 95% Confidence interval [C] = 0.059-0.117%). Dengue antibodies IgG prevalence increased with age with the lowest in 18-26 years age group (30.5%) and the highest in 56-65 years age group (73.3%). There are no significant differences for dengue seroprevalence seen when compare according to gender, localities, ethnicity and blood group. Conclusions: This result shows the high prevalence of dengue antibodies among Sabah blood donor. High-prevalence of Dengue IgG seropositivity reflects the high endemicity of dengue disease in this region of Malaysia. This finding also alerts the authorities to reconsider on adding the dengue screening in the blood screening panel for blood product to reduce the ADE risk. DENV seroprevalence among Sabah population were rather low for dengue vaccine implementation according to WHO recommendation in 2017.